2021
DOI: 10.18280/ijdne.160608
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Co-Digestion of Cow Manure and Palm Oil Mill Effluent (POME): Assessment of Methane Production and Biodegradation Efficiency

Abstract: The performance of anaerobic co-digestion of cow manure and POME was evaluated. The anaerobic composting process was carried out by using semi-continuous reactors under the mesophilic condition (35 ± 1℃). The addition of POME to the on-going anaerobic composting of cow manure was applied stepwise within a cycle of HRT (20 days). Results showed that the anaerobic co-digestion reactor could produce methane at about six times higher (7.2 L CH4) than the control reactor (1.3 L CH4). An increasing of POME loaded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Besides, study found that fungal decomposers preferred pH ranging from 5.5 to 8.0 [36]. The acidic conditions would be best favorable for the growth of fungi, and also may help degrade lignin and cellulose during the decomposition process [37][38][39].…”
Section: Figure 3 Total Nitrogen Of Composts Obtained From Different ...mentioning
confidence: 97%
“…Besides, study found that fungal decomposers preferred pH ranging from 5.5 to 8.0 [36]. The acidic conditions would be best favorable for the growth of fungi, and also may help degrade lignin and cellulose during the decomposition process [37][38][39].…”
Section: Figure 3 Total Nitrogen Of Composts Obtained From Different ...mentioning
confidence: 97%
“…Anaerobic digestion has been employed for centuries to convert organic materials into biogas, a renewable energy source primarily composed of methane and carbon dioxide [8], [9]. Traditionally, anaerobic digestion systems have focused on treating specific types of organic waste, such as sewage sludge or agricultural residues [10].…”
Section: Introductionmentioning
confidence: 99%